Analisis Keseimbangan Eksternal Indonesia: Pendekatan Intertemporal Model of Current Account - Nurmalindah, Nurmalindah; Safuan, Sugiharso (Jurnal Ekonomi dan Pembangunan Indonesia, 2013)
Current account balance has an important role of measuring the direction and the amount of international loan. This study analyzes Indonesian external balance due to its solvency condition of external debt and sustainability of current account balance during 1970-2007 by intertemporal-model approach of current account. The results of cointegration test and bivariate autoregressive (VAR) indicate that solvency condition holds, but not for the sustainability condition of current account balance. It means that Indonesia has capability to payback its external debt.